Design and Experimental Research of a New Type of Asteroid Anchoring System. (19th May 2021) - Yongbin, Wang; Wansong, Jiang; Long, Long; Qian, Zhu; Rui, Feng; Liwu, Wang
Abstract : Asteroid detection is of great significance to the study of the formation of the solar system and the origin of life. However, there are many types of asteroids, and they are far away from the earth, and the understanding of their various characteristics is not clear, which brings huge technical challenges to the landing and attachment of star catalogs. At present, the world is mainly based on surround, overflight, and short-term contact detection, and long-term attachment detection has not yet been realized. In order to solve the long-term attachment detection requirements of asteroids, focusing on the geological characteristics of various types of stars, this paper proposes a new type of asteroid attachment mechanism based on the beetle bionic theory, which can realize intelligent and flexible attachment and has strong adaptability. Around this design, this paper analyzes the mechanism of adhesion and realizes the adaptive matching of unascertained terrain landing point adhesion. On this basis, a prototype of the asteroid landing attachment mechanism was developed and verified by experiments. The experiment proved that the mechanism has strong multiterrain matching ability and can obtain an adhesion force of not less than 36 N on ordinary concrete ground.